Design and Implementation of 2×4 Truncated Corner Patch Microstrip Array Antenna with U-Slot at 2.4 GHz Frequency for Wi-Fi Applications - Koesmarijanto Koesmarijanto; Ainun Azizah; Hendro Darmono (Politeknik Negeri Malang, 2022)
Antennas are an important component in wireless communication systems that continue to grow in the use of the 2.4 GHz frequency for 4G/LTE applications. Technology in the field of telecommunications has developed very rapidly using wireless communication, which is easily accessible by various devices, for example, Wi-Fi or Wireless Fidelity. Microstrip antenna is one type of antenna that has a narrow bandwidth, small gain. This research aims to widen the bandwidth by designing and manufacturing a truncated corner microstrip patch antenna with a 2x4 array at a frequency of 2.4 GHz with a U-slot. The truncated corner method is used to obtain circular polarization. The truncated corner microstrip antenna is designed by cutting corners. The array method is used to obtain the maximum gain value, while the addition of U-slot aims to reduce the return loss and Voltage Standing Wave Ratio (VSWR) values.